2021
DOI: 10.1093/ofid/ofab588
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Effectiveness and Safety of Baricitinib as Adjunctive to Standard-of-Care Treatment in Hospitalized Patients With Severe Coronavirus Disease 2019

Abstract: Background Therapeutic options for hospitalized patients with severe coronavirus disease 2019 (sCOVID-19) are limited. Preliminary data have shown promising results with baricitinib, but real-life experience is lacking. We assessed the safety and effectiveness of add-on baricitinib to standard-of-care (SOC) including dexamethasone in hospitalized patients with sCOVID-19. Methods This study is a 2-center, observational, retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Further data from the pre‐EUA COV‐BARRIER study of hospitalized patients showed baricitinib in addition to standard of care (SOC) led to a 38.2% relative reduction in 28‐day all‐cause mortality ( p = 0.0018). 67 Similarly, studies of baricitinib in combination with SOC, remdesivir, and dexamethasone, respectively, found decreased ICU admissions (22.3% vs. 36.9%, p = 0.002) 68 and invasive mechanical ventilation was avoided in 90% of patients 69 (Table S2.2 ).…”
Section: Resultsmentioning
confidence: 95%
“…Further data from the pre‐EUA COV‐BARRIER study of hospitalized patients showed baricitinib in addition to standard of care (SOC) led to a 38.2% relative reduction in 28‐day all‐cause mortality ( p = 0.0018). 67 Similarly, studies of baricitinib in combination with SOC, remdesivir, and dexamethasone, respectively, found decreased ICU admissions (22.3% vs. 36.9%, p = 0.002) 68 and invasive mechanical ventilation was avoided in 90% of patients 69 (Table S2.2 ).…”
Section: Resultsmentioning
confidence: 95%
“…Other important members of this category are the Janus kinase inhibitors [ 63 , 64 ]. Among them, baricitinib showed promising results in hospitalized patients, especially those receiving high flow oxygen or noninvasive ventilation [ 65 , 66 ].…”
Section: Potential Use Of Cd24 In Covid-19mentioning
confidence: 99%
“…A retrospective cohort study conducted by Tziolos et al [43] in Athens, Greece assessed the role of baricitinib (4 mg/day for 14 days or discharge) as an add-on therapy to the standard of care in 369 hospitalized patients with COVID-19 which included dexamethasone (6 mg/day), remdesivir (200 mg/day on day 1 followed by 100 mg/day for subsequent days) and low molecular weight heparin for thromboprophylaxis apart from antimicrobials as per the physicians discretion. The standard of care regimen was provided to 47.7% of the patients and the remaining received baricitinib as an add-on.…”
Section: Covid-19 Drug Development -Recent Advances New Perspectives ...mentioning
confidence: 99%